The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ejn.14928
|View full text |Cite
|
Sign up to set email alerts
|

The neural mechanisms of audiotactile binding depend on asynchrony

Abstract: Imagine sitting outside on a summer evening. Suddenly you hear a buzz and then feel a prick to your skin, as the mosquito lands. You are faster to swat it away because you first heard it coming. This faster detection of a multisensory event, known as the redundant target effect (RTE) (Diederich

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(128 reference statements)
1
3
0
Order By: Relevance
“…For example, Morís Fernández et al (2015) measured fMRI data and showed that multisensory integration occurred almost exclusively only when the congruent AV speech was attended. However, Ahmed et al, (2021) measured EEG and found some evidence for early AV integration in the unattended stream, consistent with the idea that distinct audiovisual computations emerge at different processing stages (Kayser & Shams, 2015;Talsma et al, 2007;Talsma & Woldorff, 2005;Zumer et al, 2020).…”
Section: Introduction (650 Words)supporting
confidence: 68%
“…For example, Morís Fernández et al (2015) measured fMRI data and showed that multisensory integration occurred almost exclusively only when the congruent AV speech was attended. However, Ahmed et al, (2021) measured EEG and found some evidence for early AV integration in the unattended stream, consistent with the idea that distinct audiovisual computations emerge at different processing stages (Kayser & Shams, 2015;Talsma et al, 2007;Talsma & Woldorff, 2005;Zumer et al, 2020).…”
Section: Introduction (650 Words)supporting
confidence: 68%
“…Initial causal inference based on temporal correlations and coincidence alone may thus occur in sensory cortices during anesthesia (Atilgan et al 2018). Relatively simple processing units similar to the Hassenstein-Reichard motion detector (Parise & Ernst 2016) or mechanisms of phase resetting (Kayser et al 2008, Lakatos et al 2007, Mercier et al 2013, Zumer et al 2021) may potentially support the computation of multisensory coincidence, correlations, and response enhancement for nearly synchronous stimuli in early sensory areas.…”
Section: Solving the Binding Problem: Causal Inferencementioning
confidence: 99%
“…In everyday life our senses are exposed to a constant influx of sensory signals. To form a coherent percept the brain needs to bind signals that arise from a common event and treat signals separately from different events 1 7 . Temporal synchrony is a critical cue for solving this binding problem 8 11 .…”
mentioning
confidence: 99%